Android app development and design learn by video - Ehrenstein, Constantin (Peachpit Press, 2011)
"This innovative product uses interactive video to give developer/designers a solid understanding of how to design apps that can run on many different Android-based devices, under Android versions up to 2.3. Users will learn to set up an Android development environment, define device emulators, and connect to actual Android devices. The video also explains the fundamentals of Android layouts and user interfaces. It introduces the process of programming an app's interaction with Activities and Services and explains how to access existing Android system components. It also looks at how to ensure that an app runs on as many Android devices, screen sizes, and form factors as possible. It also explains how to package an app and publish it to the Android Marketplace. Experienced instructor Constantin Ehrenstein presents five hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials."--Resource description page.
Title from resource description page (viewed Aug. 15, 2011)
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing; Logiciels d'application; Développement; Informatique mobile; Application software; Development